Intake of Non-steroidal Anti-inflammatory Drugs and the Risk of Prostate Cancer: A Meta-Analysis - Shang, Zhenhua; Wang, Xue; Yan, Hao; Cui, Bo; Wang, Qi; Wu, Jiangtao; Cui, Xin; Li, Jin; Ou, Tongwen; Yang, Kun (Frontiers in Oncology, 2018)
Background: Epidemiological evidences regarding the association between the use of non-steroidal anti-inflammatory drugs (NSAIDs) and the risk of prostate cancer (PC) is still controversial. Therefore, we conducted a meta-analysis to explore the controversy that exists. Methods: Electronic databases including Medline, EMBASE, Web of Science, Cochrane Library, BIOSIS, Scopus, CBM, CNKI, WANFANG, and CQVIP were used to search for and identify eligible studies published until December 31, 2017. Pooled effect estimates for the relative risk (RR) were computed through fixed-effects or random-effects models as appropriate. Publication bias was evaluated by Egger’s and Begg’s tests and potential sources of heterogeneity were investigated in subgroup analyses. Results：A total of 43 observational studies were eligible for this meta-analysis. A protective effect was identified for the intake of any NSAIDs on the risk of PC (pooled RR = 0.89, 95 % CI = 0.81 - 0.98). Moreover, the long-term intake of NSAIDs (≥5 years rather than ≥4 years) was associated with reduced PC incidence (pooled RR = 0.882, 95% CI = 0.785 - 0.991). Aspirin intake was also associated with a 7.0% risk reduction of PC (pooled RR = 0.93, 95% CI = 0.89 - 0.96). The inverse association became stronger for advanced PC and PC with a Gleason score ≥7 compared to the association with total PC. Interestingly, it was the daily dose (≥1 pill/day) rather than, long-term aspirin intake (≥4 years or ≥5 years) that was associated with reduced PC incidence (pooled RR = 0.875, 95% CI = 0.792 - 0.967). The pooled effects for non-aspirin NSAIDs demonstrated no significantly adverse or beneficial effects on total PC, advanced PC, or PC with Gleason score ≥7, though all pooled RRs were >1. Conclusions：Our findings suggested a protective effect of the intake of any NSAIDs on the risk of PC, especially in those who took the NSAIDs for a long period. Moreover, aspirin intake was also associated with a decreased risk of PC, and there was a dose related association between aspirin intake and the risk of PC, while no significant effects of long-term aspirin intake were found on the PC incidence.